2020
DOI: 10.18047/poljo.26.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of the Croatian Red Clover Germplasm Collection

Abstract: The leaf samples of two varieties, twenty breeding populations, and seven local populations of the Croatian red clover were collected in the full flowering stage, with an aim to evaluate their phenolic content and antioxidant activity by using the spectrophotometric methods. A significant variation among the varieties/populations in the content of total phenolics and flavonoids was determined. The results demonstrated that the red clover is a rich source of phenolics and flavonoids, ranging from 38.67 to 59.96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Furthermore, all the methods presented a significant correlation between them, with high values in the Spearman correlation coefficient. Numerous studies have also reported this correlation [ 43 , 55 ].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, all the methods presented a significant correlation between them, with high values in the Spearman correlation coefficient. Numerous studies have also reported this correlation [ 43 , 55 ].…”
Section: Resultsmentioning
confidence: 58%
“…However, the presence of phenolic compounds and their distribution in the red clover vary due to many factors—origin, cultivation influences, weather conditions, plant parts, growing stages, harvesting season, etc. [ 55 ]. Therefore, it would not be entirely appropriate to compare the results of different studies.…”
Section: Resultsmentioning
confidence: 99%
“…The determined antioxidant activity (DPPH) of the red clover extract was lower compared with the results in this study by approximately 30% (controls) and 33–39% compared with samples prepared using the excipients. In other research by Horvat et al, extracts were prepared from red clover leaves of different breeding populations [ 45 ]. The results showed that on average, DPPH inhibition was 18% lower compared to our controls and 24–27% lower compared with the samples prepared using the excipients.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature have shown that both Trifolium pratense L. and Glycyrrhiza glabra L. are good antioxidants. Trifolium pratense L. is known to contain isoflavones (daidzein, genistein, formononetin, and biochanin A), which possess estrogenic effects, but antioxidant properties of extract can be related to quercetin, hyperoside, clovamides, and other phenolic compounds [ 52 ]. The reported main phenolic compounds in Glycyrrhiza glabra L. extract responsible for its antioxidant activity are also isoflavones, such as glabridin, hispaglabridin A, and 30-hydroxy-4-O-methylglabridin [ 53 ].…”
Section: Resultsmentioning
confidence: 99%